Beyond words : (University of Hawaii Press, 2000)
Asian Writers at Work presents authors from celebrated Nobel Prize winners to young, emerging writers. In essays and interviews, they discuss their aesthetics, ethics, backgrounds, working habits, and influences, producing refreshing and fascinating portraits of themselves and of the Asian writer at work. Included are short pieces representing their writing. For nearly twenty years, Manoa has presented the work of a different Asian-Pacific country or area in each issue; for the first time, it presents portraits of the writers themselves.